1999
DOI: 10.1210/mend.13.9.0349
|View full text |Cite
|
Sign up to set email alerts
|

Function of Steroidogenic Factor 1 Domains in Nuclear Localization, Transactivation, and Interaction with Transcription Factor TFIIB and c-Jun

Abstract: Normal endocrine development and function require nuclear hormone receptor SF-1 (steroidogenic factor 1). To understand the molecular mechanism of SF-1 action, we have investigated its domain function by mutagenesis and functional analyses. Our mutant studies show that the putative AF2 (activation function 2) helix located at the C-terminal end is indispensable for gene activation. SF-1 does not have an N-terminal AF1 domain. Instead, it contains a unique FP region, composed of the Ftz-F1 box and the proline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 60 publications
(67 reference statements)
3
39
0
Order By: Relevance
“…In the case of BgFTZ-F1, the box is 100% conserved compared with those of other insect homologs, with the exception of that of B. mori (Table 1). The FTZ-F1 box extends the DNA binding site of the protein and hence increases the binding specificity (Ueda et al, 1992), and also contains putative nuclear localization signals (Li et al, 1999). Given the high conservation of the DBD and the FTZ-F1 box in BgFTZ-F1, it was not surprising that the cockroach nuclear receptor bound to the recognition element PyCAAGGPyCPu, as happens with other insect FTZ-F1 homologs (Li et al, 2000;Ueda et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of BgFTZ-F1, the box is 100% conserved compared with those of other insect homologs, with the exception of that of B. mori (Table 1). The FTZ-F1 box extends the DNA binding site of the protein and hence increases the binding specificity (Ueda et al, 1992), and also contains putative nuclear localization signals (Li et al, 1999). Given the high conservation of the DBD and the FTZ-F1 box in BgFTZ-F1, it was not surprising that the cockroach nuclear receptor bound to the recognition element PyCAAGGPyCPu, as happens with other insect FTZ-F1 homologs (Li et al, 2000;Ueda et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…3B). Thus, although the p.R84C mutation is located immediately adjacent to the proposed nuclear localization sequence of SF1 (bases 89-101, (25)), it does not alter its trafficking or stability. Previous studies have confirmed the proper nuclear localization of p.G146A SF1 (20).…”
Section: Functional Characterization Of the Mutationmentioning
confidence: 91%
“…Plasmids, Recombinant Proteins, and Antibody-The following constructs have been described previously: pcDNA3.1-SF-1-HA (21), pGEX-TFIIB (8), and pS2.3H-Luc (22). Plasmids pCMV-tag2c-SUMO-1 and 5xGAL4-E1B-Luc were generously provided by Dr. H. M. Shih (National Health Research Institutes, Taiwan) and Dr. Y. S. Lin (Institute of Biomedical Sciences, Academia Sinica, Taiwan), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The C-terminal region of its DNA-binding domain is a conserved 30-amino acid basic Ftz-F1 (Fushi-tarazu factor 1) box shared by all members of the NR5 (FTZ-F1) subfamily (6,7). An FP domain (aa 78 -172), including the Ftz-F1 box and a prolinerich sequence, contains a nuclear localization signal and interacting regions for TFIIB and c-Jun and is important for the transactivation function of SF-1 (8). Unlike other nuclear receptors, SF-1 lacks the N-terminal A/B region, which usually contains the ligand-independent transactivation AF-1 domain.…”
mentioning
confidence: 99%